Proposed pathway for patients undergoing enhanced recovery after spinal surgery: protocol for a systematic review - Ana Licina; Andrew Silvers; Harry Laughlin; Jeremy Russell; Crispin Wan (Systematic Reviews, 2020)
Abstract Background The best evidence-enhanced recovery care pathway is yet to be defined for patients undergoing spinal surgery. Minimally invasive surgery, multimodal analgesia, early mobilization, and early postoperative nutrition have been considered as critical components of enhanced recovery in spinal surgery (ERSS). The objective of this study will be to synthesize the evidence underpinning individual components of a proposed multidisciplinary enhanced recovery pathway for patients undergoing spinal surgery. Methods This is the study protocol for a systematic review of complex interventions. Our team identified 22 individual care components of a proposed pathway based on clinical practice guidelines and published reviews. We will include systematic reviews and meta-analysis, randomized controlled trials, non-randomized controlled trials, and observational studies in adults or pediatric patients evaluating any one of the pre-determined care components. Our primary outcomes will be all-cause mortality, morbidity outcomes (e.g., pulmonary, cardiac, renal, surgical complications), patient-reported outcomes and experiences (e.g., pain, quality of care experience), and health services outcomes (e.g., length of stay and costs). We will search the following databases (1990 onwards) MEDLINE, EMBASE, and Cochrane Library (Cochrane Database of Systematic Reviews and CENTRAL). Two reviewers will independently screen all citations, full-text articles, and abstract data. Potential conflicts will be resolved through discussion. The risk of bias for individual studies will be appraised using appropriate tools. A narrative synthesis will be provided with the information presented in the text and tables to summarize and explain the characteristics and findings of the included studies. Due to clinical and methodological heterogeneity, we do not anticipate to conduct meta-analyses. Confidence in cumulative evidence for each component of care will be classified according to the GRADE system. Discussion This systematic review will identify, evaluate, and integrate the evidence underpinning individual components of a pathway for patients undergoing spinal surgery. The formation of an evidence-based pathway will allow for the standardization of clinical care delivery within the context of enhanced recovery in spinal surgery. Systematic review registration PROSPERO CRD42019135289